A comparison in knee flexor and extensor strength following ACL reconstruction in international, male soccer players receiving patellar tendon or hamstrings grafts - Andreja Milutinović; Vladimir Jakovljević; Milinko Dabović; Aaron Scanlan; Dragan Radovanović; Aleksandra Orlova; Emilija Stojanović (Biology of Sport, 2023)
The aim of this study was to compare knee extensor and flexor strength recovery following anterior cruciate ligament (ACL) reconstruction between bone-patellar tendon-bone (BPTB) and hamstring tendon (HT) grafts in international male soccer players undergoing comparable 6-month rehabilitation programmes. Seventeen players underwent ACL reconstruction with either an autogenous BPTB graft or HT graft. Knee extensor and flexor peak torques were measured at 3 months and 6 months in the injured and contralateral legs following surgery using isokinetic dynamometry. The moderate –large asymmetries in knee extensor peak torque between legs at 3 months across graft types (BPTB: p = 0.002, g = -0.94; HT: p = 0.02, g = -0.55) were reduced to trivial asymmetries at 6 months (BPTB: p = 0.30, g = -0.19; HT: p = 0.40, g = -0.16), with a non-significant difference in limb symmetry index (LSI) between grafts at 6 months (p = 0.62, g = -0.24). Similarly, moderate–large asymmetries in knee flexor peak torque between legs at 3 months across graft types (BPTB: p = 0.13, g = -0.50; HT: p = 0.01, g = -0.97) were reduced to trivial-small asymmetries at 6 months (BPTB: p = 0.25, g = 0.18; HT: p = 0.01, g = -0.47); however, a superior LSI was evident with BPTB compared to HT grafts at 6 months (p = 0.007, g = 1.43, large ). Strength and conditioning professionals working with soccer players who are rehabilitating from ACL reconstruction after receiving a HT graft should give adequate attention to delivering suitable hamstring exercises that ensure optimal strength restoration.